How Phenolic Compounds Profile and Antioxidant Activity Depend on Botanical Origin of Honey—A Case of Polish Varietal Honeys - Katarzyna Jaśkiewicz; Teresa Szczęsna; Jacek Jachuła (Molecules)
Honey contains natural biologically active compounds, and its preventive and healing properties are primarily linked to its antioxidant activity. The antioxidant properties of honey can be related to the botanical origin and content of phenolic compounds. We tested 84 honey samples from Poland, representing eight honey varieties: acacia, phacelia, buckwheat, linden, rapeseed, heather, goldenrod, and honeydew. High-performance liquid chromatography with photodiode-array detection (HPLC-DAD) was used to determine the phenolic compound composition of honey extracts. Total phenolic compounds (TPC) and DPPH radical-scavenging activity were also evaluated. We detected vanillin aldehyde, vanillic acid, caffeic acid, p-coumaric acid, and trans-ferulic acid, as well as flavonoid pinocembrin, in all honey varieties. The results of our study showed that honeys with high antioxidant activity were characterized by significantly higher total phenolic compounds content. Neither clustering method nor principal component analysis (PCA) showed clear separation of each honey variety, possibly due to high intra-variety diversities. We suppose that the variability of qualitative and quantitative phenolic compound composition within honey varieties may result from the region of origin, secondary nectar sources, and the time of harvest.